Karakteristik dan Potensi Sedimen di Muara Sungai Kampar - Edison '; Mubarak '; Lamun Bathara (Universitas Riau, 2009)
This research was conducted on June 2009, located in Estuary Kampar Rivers, Pelalawan Regency, Riau Province. It was aimed to understand study andanalyze the characteristics of the sediment and the possible applicability in the Kampar River Estuary. Results of laboratory analysis of sediment samples obtainedgrain size distribution of five types of sediment texture, namely: sand, sand silt,sandy silt, silt, and sandy mud. Heavy mineral analysis of heavy minerals obtained 9,3 light mineral, and clay minerals. Heavy minerals obtained in the form of magnetite,kasiterit, zircon, tourmalin, pyrite, amfibole, ilmenite markasit, and pyroxene,whereas for minor minerals, namely quartz, muscovite, and biotite. Chemicalanalysis of sediment samples obtained rare earth elements, such as tantalum, ytrium,zirconium, and content kasiterit associated with other minerals.Key words : Sediment, Sand, Bono